Description of a new subspecies of Pseudostrangalia cruentata (Haldeman, 1847) (Coleoptera, Cerambycidae, Lepturinae) from the United States of America - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2025)
A new subspecies of Pseudostrangalia cruentata (Haldeman, 1847) is described from the state of Texas, United States of America. Some biological information about the new subspecies is provided.